Lithium ion battery
By adding hard carbon to the negative electrode active substance of lithium-ion batteries and adjusting the relationship between its mass percentage content and the overhang area proportion, the problem of insufficient power performance in high-power applications is solved, and better power performance and safety are achieved.
Patent Information
- Application Number
- CN202411982881.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing lithium-ion batteries have insufficient power performance in high power applications, especially when vehicles start and brake, requiring high starting current and rapid energy recovery.
The negative electrode active material containing hard carbon is used, and the relationship between the percentage of hard carbon mass content and the proportion of overhang area is adjusted, the conditions of 0.003≤A×B≤0.036 are met to improve the power performance of lithium-ion batteries.
It significantly improves the power performance of lithium-ion batteries, shortens the overall transmission path between the positive and negative electrodes, and ensures the safety and high power characteristics of the battery.
Smart Images

Figure CN119864484A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a lithium ion battery. Background Art
[0002] With the widespread application of lithium-ion batteries, more stringent requirements are placed on product performance. Many application scenarios, such as hybrid vehicles, have both internal combustion engines and power batteries as drive systems. A large starting current is required when the vehicle starts, and energy needs to be recovered in a very short time when braking. The power requirements for lithium-ion batteries are relatively high. Therefore, exploring more advanced high-power lithium-ion battery technology has become a key issue in the current field. Summary of the invention
[0003] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a lithium ion battery. The lithium ion battery of the present invention can exert good power performance.
[0004] A first aspect of the present invention provides a lithium ion battery, the lithium ion battery comprising a negative electrode sheet and a positive electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active coating located on at least one side of the surface of the negative electrode current collector; the positive electrode sheet comprising a positive electrode current collector and a positive electrode active coating located on at least one side of the surface of the positive electrode current collector; the lithium ion battery is a laminated battery; in the thickness direction of the negative electrode sheet, the negative electrode active coating at least partially covers the positive electrode active coating; the negative electrode sheet comprises a negative electrode ear, and the positive electrode sheet comprises a positive electrode ear;
[0005] The lithium-ion battery comprises a negative electrode ear and a positive electrode ear, and along a first direction, the negative electrode sheet is connected to the negative electrode ear, and the positive electrode sheet is connected to the positive electrode ear;
[0006] The negative electrode sheet includes an overhang area, which refers to the portion of the negative electrode sheet corresponding to the non-overlapping area of the projections of the negative electrode active coating and the positive electrode active coating along the thickness direction of the negative electrode sheet, and the percentage of the area of the overhang area to the total area of the negative electrode sheet is recorded as A;
[0007] The negative electrode active coating comprises a negative electrode active material, the negative electrode active material comprises hard carbon, and the mass percentage content of the hard carbon in the negative electrode active material is recorded as B;
[0008] A and B satisfy the relationship: 0.003≤A×B≤0.036.
[0009] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0010] (1) The negative electrode active material of the present invention uses hard carbon with a large negative electrode interlayer spacing, which can effectively improve the power performance of lithium-ion batteries;
[0011] (2) The present invention adjusts the relationship between the mass percentage of hard carbon in the negative electrode active material and the area ratio of the overhang region to satisfy the relationship: 0.003≤A×B≤0.036. This can shorten the overall transmission path of lithium ions between the positive and negative electrodes while ensuring safety, so that the lithium-ion battery including the negative electrode sheet can exert better power performance.
[0012] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 FIG. 1 is a schematic diagram of a cross-sectional structure of a positive electrode sheet and a negative electrode sheet along a first direction in an example of the present invention;
[0014] Figure 2 The figure shows a schematic diagram of the structure of the positive electrode sheet and the negative electrode sheet from a top view in one embodiment of the present invention;
[0015] Figure 3 Shown is a front SEM schematic diagram of a negative electrode sheet in an example of the present invention.
[0016] Description of reference numerals:
[0017] Negative electrode sheet 100 , negative electrode current collector 110 , negative electrode active coating 120 , positive electrode sheet 200 , positive electrode current collector 210 , positive electrode active coating 220 , insulating layer 230 . DETAILED DESCRIPTION
[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0019] Lithium-ion batteries have the advantages of high energy density, low self-discharge, long life, near-zero memory, light weight, and environmental protection. They are widely used in portable devices, electric vehicles, aerospace and other fields, and have gained commercial recognition. Many applications, such as hybrid vehicles, have both internal combustion engines and power batteries as drive systems. When the vehicle starts, a large starting current is required, and when braking, energy needs to be recovered in a very short time. The power requirements for the battery are high, so the development of high-output lithium-ion batteries is eagerly anticipated.
[0020] Therefore, based on the above problems, the present invention provides a lithium ion battery, and the lithium ion battery of the present invention can exert better power performance.
[0021] A first aspect of the present invention provides a lithium ion battery, the lithium ion battery comprising a negative electrode sheet and a positive electrode sheet, such as Figure 1 As shown, it is a schematic diagram of the cross-sectional structure of a positive electrode sheet and a negative electrode sheet along a first direction of an example of the present invention; the negative electrode sheet 100 includes a negative electrode collector 110 and a negative electrode active coating 120 located on at least one side of the surface of the negative electrode collector 110; the positive electrode sheet 200 includes a positive electrode collector 210 and a positive electrode active coating 220 located on at least one side of the surface of the positive electrode collector 210; the lithium-ion battery is a laminated battery; in the thickness direction of the negative electrode sheet 100, the negative electrode active coating 120 at least partially covers the positive electrode active coating 220; wherein, a laminated battery refers to a battery structure in which a battery unit is formed by assembling a positive electrode sheet, a negative electrode sheet and a diaphragm material in a stacked manner; it can be understood that the lithium-ion battery also includes a positive electrode ear and a negative electrode ear, each of which is connected to the edge of the positive electrode sheet and the negative electrode sheet in the first direction, and according to the actual shape of the electrode sheet, the first direction can be the width direction of the electrode sheet or the length direction of the electrode sheet.
[0022] The negative electrode sheet includes an overhang area, which refers to the portion of the negative electrode sheet corresponding to the non-overlapping area of the projections of the negative electrode active coating 120 and the positive electrode active coating 220 along the thickness direction of the negative electrode sheet, and the percentage of the area of the overhang area to the total area of the negative electrode sheet is recorded as A;
[0023] The negative electrode active coating comprises a negative electrode active material, the negative electrode active material comprises hard carbon, and the mass percentage content of the hard carbon in the negative electrode active material is recorded as B;
[0024] A and B satisfy the relationship: 0.003≤A×B≤0.036, for example, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.011, 0.012, 0.013, 0.014, 0.015, 0.016, 0.017, 0.018, 0.019, 0.02, 0.021, 0.022, 0.023, 0.024, 0.025, 0.026, 0.027, 0.028, 0.029, 0.03, 0.031, 0.032, 0.033, 0.034, 0.035 or 0.036.
[0025] In one example, 0.008≤A×B≤0.028.
[0026] In yet another example, 0.011≤A×B≤0.022.
[0027] At present, the negative electrode of commercial lithium-ion batteries is mainly made of graphite materials. According to the lithium storage mechanism of LiC6 between graphite layers, its theoretical specific capacity is only 365-382mAh / g, and the room for improvement is very limited. In addition, the lithium diffusion between graphite layers also restricts its rate performance. As a new type of negative electrode material, hard carbon has a similar lithium potential and higher specific capacity as graphite. By adding hard carbon to the negative electrode active material, the gram capacity of the negative electrode sheet can be significantly improved. In general, the gram capacity of the negative electrode sheet containing hard carbon will be 20%-35% higher than that of the graphite negative electrode sheet. The high gram capacity of the negative electrode sheet helps the battery release more electrical energy in a short time, providing a basis for power output for improving the power performance of lithium-ion batteries and meeting the current demand for high power. More importantly, hard carbon is composed of a graphite-like microcrystalline structure and open angular microcrystals. This unique microcrystalline structure can not only provide more lithium storage sites, but also the hard carbon negative electrode has a large interlayer spacing, which is conducive to the intercalation and deintercalation of lithium ions between the layers, thereby improving the charge and discharge capacity and rate performance of the negative electrode active material, thereby effectively improving the output power of the lithium-ion battery, giving it excellent power performance.
[0028] Further, when the ratio of the negative electrode capacity to the positive electrode capacity is greater than 1, that is, the N / P ratio>1.0, it can be ensured that the negative electrode capacity has a certain redundancy compared with the positive electrode capacity, and the precipitation of lithium dendrites can be avoided, which is beneficial to the performance of the positive electrode capacity of the lithium ion battery, and the initial discharge capacity of the battery is improved, thereby helping to improve the power performance of the lithium ion battery. The present invention significantly improves the gram capacity of the negative electrode sheet by adding hard carbon to the negative electrode active material, and as the gram capacity of the negative electrode sheet increases, the N / P ratio of the positive and negative electrode sheets will also increase accordingly, satisfying the ratio of the negative electrode capacity to the positive electrode capacity greater than 1, but when the difference in the capacity of the positive and negative electrode sheets is too large, it may cause uneven lithium ion transmission between the positive and negative electrode sheets, affecting the charge and discharge efficiency and kinetic performance of the battery. Therefore, it is necessary to avoid the adverse effects caused by the increase in the gram capacity of the negative electrode sheet by reducing the difference in the capacity of the positive and negative electrodes. Specifically, the present invention finds that it can be achieved by reducing the area ratio A of the overhang area, but as the area percentage A of the overhang area decreases, the area of the negative electrode active material exceeding the positive electrode sheet is too small, affecting the safety performance of the lithium ion battery.
[0029] In summary, in order to better control the N / P ratio of the negative electrode sheet within an appropriate range (greater than 1.0, generally about 1.06 to 1.10, but this range will vary according to the specific selection of different positive and negative electrode materials, the coating accuracy of the equipment and other factors) to ensure the safety performance of lithium-ion batteries, the present invention adjusts the relationship between the hard carbon mass percentage content B in the negative electrode active material and the area percentage A of the overhang area so that the two satisfy the relationship: 0.003≤A×B≤0.036. When the area percentage A of the overhang area becomes smaller and the N / P ratio decreases more, the mass percentage content B of the hard carbon in the negative electrode active material can be increased to match the positive and negative electrode capacities to prevent the battery power performance from deteriorating. When more hard carbon is added to the negative electrode active material and the N / P ratio of the positive and negative electrode sheets is too large, the positive and negative electrode capacities can be matched by correspondingly reducing the area of the overhang area. Moreover, by controlling the N / P ratio within a suitable range, the lithium plating of the negative electrode sheet can be alleviated, thereby avoiding the damage of the SEI film and the battery separator caused by the precipitation of lithium dendrites, and significantly improving the safety performance of lithium-ion batteries; in addition, it can also greatly increase the utilization rate of the negative electrode active material, reduce the consumption of the overhang area of the negative electrode sheet, avoid dead lithium, and ensure the deintercalation of lithium ions at the edge of the electrode sheet, so that the lithium-ion battery including the negative electrode sheet can exert better power performance.
[0030] In the present invention, A is 6%-12%, for example, 6%, 7%, 8%, 9%, 10%, 11% or 12%. When A is greater than 12%, the difference in capacity between the positive and negative electrodes will be too large, the overall migration path of lithium ions will increase, the charging and discharging efficiency and kinetic performance of the battery will be affected, and the current collector will be wasted, reducing the overall energy density of the battery; and when A is less than 6%, it is very likely that the electrode will short-circuit during the charge and discharge cycle; therefore, it is necessary to reasonably control the area ratio A of the overhang area so that it is within a suitable range to ensure that the lithium-ion battery has good power performance and excellent safety and economy.
[0031] In one example, the A is 8%-10%.
[0032] In the present invention, the B is 5%-30%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%. The hard carbon negative electrode material has a highly disordered carbon layer structure inside, and a large number of defects are generated inside, which is Li + Provides numerous embedding points to achieve Li + The fast embedding of hard carbon layers and the large spacing between hard carbon layers will not cause the deposition of lithium ions, which is conducive to the deintercalation of high-power lithium ions, thereby improving the charge and discharge capacity and rate performance of negative electrode active materials, and effectively improving the power performance of lithium-ion batteries. In addition, due to the large spacing between hard carbon layers, the embedding and deintercalation of lithium ions will hardly shrink or expand, and will not cause changes in the crystal structure of lithium nickel cobalt manganese oxide, avoiding the problem of damage to the electrode structure due to volume strain of battery materials, and can improve the high-temperature cycle capacity of lithium-ion batteries. However, when the mass percentage content B of hard carbon in the negative electrode active material is greater than 30%, due to the problems of low density, large slope of voltage curve and low coulomb efficiency of hard carbon materials, it is easy to cause the lithium-ion battery to produce a large irreversible capacity during the first charge, which seriously affects the improvement of the energy density of the lithium-ion battery. In addition, the low compaction density of hard carbon materials is not conducive to the improvement of the volume energy density of lithium-ion batteries. Therefore, hard carbon is not suitable for excessive use in negative electrode active materials; and when the mass percentage content B of hard carbon in the negative electrode active material is less than 5%, it will lead to a weakened improvement effect on the charge and discharge capacity and rate performance of the negative electrode active material, which is not conducive to improving the power performance of lithium-ion batteries. Therefore, it is necessary to control the doping mass percentage content of hard carbon in the negative electrode active material within an appropriate range, so that the lithium-ion battery including the negative electrode sheet of the present invention has excellent power performance.
[0033] In one example, the B is 10%-30%.
[0034] In the present invention, the negative electrode active material further includes other negative electrode active materials, and the other negative electrode active materials may include carbon-based negative electrode materials such as artificial graphite and soft carbon.
[0035] In the present invention, the mass percentage content of the other negative electrode active materials in the negative electrode active materials is 70%-95%.
[0036] In one example, the mass percentage content of the other negative electrode active materials in the negative electrode active materials is 75%-90%.
[0037] In the present invention, the width of the overhang area of the negative electrode sheet at any side edge in the first direction is 0.1mm-5mm, for example, 0.1mm, 0.5mm, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, 2mm, 2.1mm, 2.2mm, 2.3mm, 2.4mm, 2.5mm, 2.6mm, 2.7mm, 2.8mm, 2.9mm, 3mm, 3.5mm, 4mm, 4.5mm or 5mm.
[0038] In one example, the width of the overhang area of the edge of any side of the negative electrode sheet in the first direction is 1 mm-3 mm.
[0039] In the present invention, if Figure 1 As shown, on the positive electrode sheet 200 along the first direction, the positive electrode current collector 210 includes a positive electrode active area and a positive electrode inactive area, the positive electrode inactive area is located at one side edge of the positive electrode sheet 200 in the first direction, the positive electrode active area is connected to the positive electrode inactive area, the positive electrode active coating 220 is arranged in the positive electrode active area, and the positive electrode inactive area is arranged with an insulating layer 230;
[0040] like Figure 1 and Figure 2 As shown, Figure 2 This is a schematic diagram of the structure of the positive electrode sheet and the negative electrode sheet in an example of the present invention from a top view. Compared with the side edge of the negative electrode sheet 100 close to the positive electrode inactive area and the side edge of the positive electrode inactive area away from the positive electrode active area, along the first direction, the side edge of the negative electrode sheet close to the positive electrode inactive area does not exceed the side edge of the positive electrode inactive area away from the positive electrode active area, that is, one side edge of the negative electrode sheet 100 falls within the positive electrode inactive area where the insulating layer 230 is located.
[0041] The short circuit between the positive electrode collector and the negative electrode active coating is the most dangerous short circuit mode. Once it occurs, it will greatly limit the power output of the lithium-ion battery and affect the power performance of the lithium-ion battery. Moreover, because the excessive current generated by the short circuit will cause the internal temperature of the battery to rise, it is easy to cause safety accidents such as overheating, fire and even explosion, affecting the stability and reliability of lithium-ion batteries in high-power applications.
[0042] The present invention provides a positive electrode inactive region containing an insulating layer at one side edge of the positive electrode collector, and makes one side edge of the negative electrode sheet fall within the positive electrode inactive region containing the insulating layer, thereby effectively avoiding a short circuit between the positive electrode collector and the negative electrode active coating, significantly reducing the risk of short circuit within the battery, thereby improving the safety of the lithium-ion battery, providing a stable and reliable application basis for high-power lithium-ion batteries, and further improving the high-power characteristics of the lithium-ion battery of the present invention.
[0043] However, correspondingly, compared with the die-cutting of the positive electrode active coating, burrs are more likely to be generated during the die-cutting of the insulating layer, and there may also be a risk of piercing the diaphragm and causing a short circuit. Therefore, in the present invention, along the first direction, the edge of the positive electrode inactive area away from the positive electrode active area exceeds the edge of the negative electrode sheet close to the positive electrode inactive area by 0.5mm-3mm, for example, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, 2mm, 2.1mm, 2.2mm, 2.3mm, 2.4mm, 2.5mm, 2.6mm, 2.7mm, 2.8mm, 2.9mm or 3mm. The present invention makes the side of the inactive area of the positive electrode sheet closer to the edge of the negative electrode sheet exceed the edge of the negative electrode sheet by a certain distance, that is, the side edge of the insulating layer with die-cutting burrs exceeds the edge of the negative electrode sheet by 0.5mm-3mm, which can avoid the problem of piercing the diaphragm short circuit caused by the die-cutting burrs of the ceramic glue in the insulating layer. At the same time, the ceramic glue can also play a good insulating role, thereby ensuring the safety of the battery cell. In one example, the side edge of the positive inactive area along the first direction of the positive electrode sheet away from the positive active area exceeds the same side edge of the negative electrode sheet by 0.8mm-2.8mm.
[0044] In summary, the design of the positions of the positive and negative electrodes and the insulating layer of the present invention effectively improves the safety of lithium-ion batteries, provides a stable and reliable application basis for high-power lithium-ion batteries, and enables them to exert better power performance.
[0045] Furthermore, in the present invention, the width ratio of the negative electrode sheet to the positive electrode active area in the first direction is (1.03-1.08):1, for example, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1 or 1.08:1.
[0046] In the present invention, the area ratio of the negative electrode sheet to the positive electrode active area is (1-1.1):1, for example, 1:1, 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1, 1.08:1, 1.09:1 or 1.1:1.
[0047] By further adjusting the width ratio of the negative electrode sheet to the positive electrode active area in the first direction of the positive electrode sheet and the area ratio corresponding thereto, the length of the negative electrode sheet and the area of the part of the first direction beyond the positive electrode sheet, that is, the area of the overhang area, can be further adjusted, thereby reducing the formation of lithium dendrites and further improving the safety of lithium-ion batteries. However, the overhang area itself does not participate in the electrochemical reaction, which means that the total energy output of the negative electrode sheet will be reduced relative to its volume or mass, thereby causing the energy density of the battery to decrease. The present invention can optimize the overall energy density of the battery through reasonable design by adjusting the width ratio of the negative electrode sheet to the positive electrode active area and the area ratio corresponding thereto, while ensuring high safety, it has excellent overall energy density.
[0048] In the present invention, the positive electrode active coating comprises a positive electrode active material, and the positive electrode active material comprises Li (1+x) Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; wherein M is at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr, and the positive electrode active material includes secondary particles formed by primary particles. The secondary particles of the positive electrode active material of the present invention can be formed by agglomerating the primary particles of the positive electrode active material.
[0049] The charging and discharging mechanism of lithium-ion batteries is achieved through positive and negative electrode reactions. For high-power batteries, the specific material selection of the positive and negative electrodes and the matching of the particle sizes are particularly important for high-rate charging and discharging. The positive electrode active material of the present invention adopts the ternary material described in the above chemical formula, and is matched with a negative electrode active material system containing hard carbon, which can effectively improve the lithium ion diffusion coefficient of the positive electrode active material and improve the charging and discharging capacity and rate performance of the lithium-ion battery; this is because the negative electrode active material system containing hard carbon has a larger negative electrode interlayer spacing than the negative electrode active material system of pure graphite, and is used together with the positive electrode active material, which is more conducive to the deintercalation of high-power lithium ions and improves the lithium ion diffusion coefficient, thereby further improving the rate performance of the lithium-ion battery.
[0050] In one example, the ratio of the particle size Dv50 of the positive electrode active material to the particle size Dv50 of the hard carbon is 1:(1-2.1), for example, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2 or 1:2.1. The ratio of the particle size Dv50 of the positive electrode active material to the particle size Dv50 of the hard carbon is 1:(1-2.1).
[0051] The particle size Dv50 of the above particles can be obtained by taking the average value after testing with a particle size tester. The test method is: using Malvern MS3000, setting the test conditions as follows: refractive index 2.1, absorptivity 1.0, shading 8-12%, water (or ethanol) as the dispersant, stirring rate 2500rpm, testing 3 times respectively, and then taking the average value to obtain the particle size Dv50 value of the above particles.
[0052] In another example, the ratio of the particle size Dv50 of the positive electrode active material to the particle size Dv50 of the hard carbon is 1:(1.2-2).
[0053] Furthermore, since the matching of the positive and negative electrode particle sizes has a great influence on the high-rate charge and discharge of lithium-ion batteries, the high-rate discharge capability of lithium-ion batteries can be improved by adjusting the ratio range between the particle size Dv50 of the positive electrode active material and the particle size Dv50 of the hard carbon, thereby further improving the power performance of lithium-ion batteries.
[0054] In the present invention, the particle size Dv50 of the positive electrode active material is 3.5 μm-4.5 μm, for example, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9 μm, 4 μm, 4.1 μm, 4.2 μm, 4.3 μm, 4.4 μm or 4.5 μm.
[0055] In one example, the particle size Dv50 of the positive electrode active material is 3.6 μm-4.2 μm.
[0056] In the present invention, the particle size Dv50 of the hard carbon is 2μm-3.5μm, for example, 2μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm or 3.5μm.
[0057] In one example, the particle size Dv50 of the hard carbon is 2.5 μm-3.2 μm.
[0058] In the present invention, the lithium ion battery further comprises an electrolyte, the electrolyte comprises 1,3-propane sultone, and based on the total mass of the electrolyte, the mass percentage content of 1,3-propane sultone in the electrolyte is C; based on the total mass of the positive electrode active material, the mass percentage content of the element Co in the positive electrode active material is D;
[0059] The C and the D satisfy the relationship: 0.05≤C / D≤0.12, such as 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11 or 0.12. In one example, 0.06≤C / D≤0.10.
[0060] The positive active material has the problem of water absorption and side reaction under high voltage. The 1,3-propane sultone (PS) additive added to the electrolyte can improve the high temperature performance of the electrolyte and inhibit the occurrence of side reactions, thereby alleviating the gas production problem and reducing the internal resistance of the battery; the element Co can inhibit the phase change during the charge and discharge process of the battery core, but too high a content will oxidize the electrolyte, causing the high temperature cycle / storage performance of the lithium ion battery to deteriorate. PS is beneficial to the high temperature cycle / storage performance of the lithium ion battery, but too much PS will damage the rate performance of the battery, so it is necessary to control the amount of both to ensure that the battery has good high temperature cycle and storage capacity. Therefore, the present invention can significantly improve the storage gas production of the lithium ion battery by further controlling the mass percentage content C of 1,3-propane sultone in the electrolyte and the mass percentage content D of the element Co in the positive active material, greatly improving the cycle life of the lithium ion battery, thereby avoiding the adverse effects of selecting the positive active material as the positive material matched with the hard carbon negative active material system, and further contributing to stabilizing the high power performance of the lithium ion battery of the present invention.
[0061] In the present invention, the C is 0.6%-1.5%, for example, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%. When the mass percentage content C of 1,3-propane sultone is greater than 1.5%, it may cause the viscosity of the electrolyte to increase and the internal resistance of the battery to increase; when the mass percentage content C of 1,3-propane sultone is less than 0.6%, it is not possible to well inhibit the occurrence of side reactions in the electrolyte, especially lithium-ion batteries under high power will have bloating problems due to the aggravation of side reactions, affecting the cycle performance and power performance of lithium-ion batteries. Therefore, it is necessary to control the mass percentage content C of 1,3-propane sultone within an appropriate range.
[0062] In one example, the C is 0.8%-1.3%.
[0063] In the present invention, D is 11%-13%, for example, 11%, 11.1%, 11.2%, 11.3%, 11.4%, 11.5%, 11.6%, 11.7%, 11.8%, 11.9%, 12%, 12.1%, 12.2%, 12.3%, 12.4%, 12.5%, 12.6%, 12.7%, 12.8%, 12.9% or 13%. Element Co can inhibit the phase change of the battery cell charge and discharge process, stabilize the layered structure of the positive active material, reduce the impedance value of the positive electrode sheet, and improve the conductivity of the positive electrode sheet, thereby effectively improving the cycle performance and power performance of the lithium ion battery. However, when the mass percentage content D of the element Co in the positive electrode active material is less than 11%, Li-Ni mixing will occur in the material and the synthesis of the positive electrode active material will be difficult; when the mass percentage content D of the element Co in the positive electrode active material is greater than 13%, the electrolyte will be oxidized, causing a decrease in the high temperature performance of the lithium-ion battery; therefore, it is necessary to control the mass percentage content D of the element Co in the positive electrode active material within an appropriate range, which helps to improve the adverse effects of adjusting the mass percentage content D of the element Co in the positive electrode active material.
[0064] In one example, the D is 11.3%-12.8%.
[0065] In the present invention, the insulating layer includes ceramic glue, and the ceramic glue includes polymer resin and filler. The ceramic glue may also include other additives such as curing agent, diluent, toughening agent or coupling agent, and the other additives may be selected from additives conventionally used in the art.
[0066] In one example, the polymer resin includes at least one of polyester, epoxy resin, polyurethane, polybutadiene acid, silicone, polyesterimide, and polyimide.
[0067] In one example, the filler includes at least one of boehmite, SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, Al(OH)3, Mg(OH)2 and SiC.
[0068] In one embodiment, the ceramic glue is AT9 ceramic glue.
[0069] In the present invention, the negative electrode active coating of the negative electrode sheet may further include a binder and a conductive agent; in the present invention, the positive electrode active material of the positive electrode sheet may also include a binder and a conductive agent. The binder and the conductive agent may be prepared by conventional methods in the art or obtained commercially.
[0070] In the present invention, the lithium-ion secondary battery further comprises a separator, and the separator can be prepared by conventional methods in the art or obtained commercially.
[0071] In the present invention, the electrolyte also includes an organic solvent, an additive and an electrolyte lithium salt, and the electrolyte lithium salt includes at least one of lithium hexafluorophosphate, bis(fluorosulfonyl)imide lithium salt, lithium tetrafluoroborate and lithium difluorooxalatoborate; the organic solvent includes at least one of N-methylpyrrolidone (NMP), carbonates, ethers and amides, and the additives may include various additives commonly used in the art.
[0072] In the present invention, the lithium-ion battery may be a Z-type stacked battery including a continuous separator, or an E-type stacked battery including multiple separators.
[0073] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0074] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.
[0075] Example 1
[0076] (1) Preparation of positive electrode
[0077] The ternary material 613NCM (LiNi 0.6 Co 0.1 Mn 0.3O2) as the positive electrode active material, the positive electrode active material, conductive carbon black, PVDF, in a ratio of 95.5%:3.5%:1%, are uniformly dispersed by high-speed stirring to form a mixture containing the positive electrode active material, wherein the particle size Dv50 of the positive electrode active material is 4μm. The mixture uses NMP (N-methylpyrrolidone) as a solvent to form a positive electrode active material slurry, and the solid content in the slurry is 60%. The slurry is evenly coated on both sides of the aluminum foil to form a positive electrode active coating, and at the same time, a 4mm AT9 ceramic glue is coated on one side of the slurry to form an insulating layer. After drying and roller pressing, a positive electrode sheet is obtained.
[0078] (2) Preparation of negative electrode
[0079] Active materials artificial graphite, hard carbon, binder (SBR, styrene-butadiene rubber) and conductive agent (conductive carbon black) are mixed and stirred at high speed to obtain a uniform dispersion to form a mixture containing negative electrode active materials. In the mixture, the solid components include 80% artificial graphite, 15% hard carbon, 2% conductive agent, and 3% binder SBR, wherein the particle size Dv50 of the hard carbon is 2.5 μm. According to step (1), it can be calculated that the ratio of the particle size Dv50 of the positive electrode active material to the particle size Dv50 of the hard carbon is 1.6:1. Water is used as a solvent to prepare a negative electrode active material slurry with a solid content of 45%. The slurry is evenly coated on both sides of the copper foil, and after drying and roller pressing, a negative electrode sheet is obtained. The SEM schematic diagram of the negative electrode sheet is shown as follows. Figure 3 shown.
[0080] (3) Pole die cutting
[0081] The positive electrode sheet obtained in step (1) is punched into 67 (63 mm paste + 4 mm insulating glue) mm*45 mm; the negative electrode sheet obtained in step (2) is punched into 66 mm*47 mm; the percentage value A of the overhang area to the total area of the negative electrode sheet is 8.6%, wherein the width of the overhang area at one edge of the negative electrode sheet close to the insulating layer of the positive electrode sheet is 2 mm, and the width of the overhang area at the other edge is 1 mm, the width ratio of the negative electrode sheet to the positive electrode active area in the first direction of the positive electrode sheet is 1.05:1, and the area ratio of the negative electrode sheet to the positive electrode active area is 1.09:1.
[0082] (4) Battery assembly
[0083] The bare cell is formed by Z-type lamination, where Figure 2 As shown, Figure 2The schematic diagram of the top view of the positive and negative electrodes is shown in Figure 1. The edge of the positive electrode active coating (active area) of the positive electrode is 2 mm lower than the edge of the negative electrode in the same direction. The edge of the insulating layer (inactive area) of the positive electrode is 2 mm higher than the edge of the negative electrode in the same direction. The aluminum tab and the copper-plated nickel tab are respectively turned out. The bare cell is clamped with a glass clamp with a strength of 100 MPa / m. 2 , and baked at 85℃ for 24 hours in vacuum, and then packaged with aluminum plastic film. The electrolyte uses 1M lithium hexafluorophosphate electrolyte, the solvent is a mixed solvent of ethylene carbonate / dimethyl carbonate / 1,2-propylene glycol carbonate in a ratio of 1:1:1 (volume ratio), and 1% 1,3-propane sultone (PS) is used as an additive. After packaging, the battery is formed and aged to obtain a square soft-package battery with a length, width and thickness of 7.8mm×50mm×75mm.
[0084] For other settings of Example 1, please refer to Table 1 and Table 2.
[0085] Example 2 Group
[0086] The second embodiment was carried out in accordance with the first embodiment, except that the mass percentage content B of the hard carbon in the negative electrode active material was changed. For details, see Table 1 and Table 2:
[0087] Example 2-1: (2) Preparation of negative electrode sheet: The active material contains 65% artificial graphite, 30% hard carbon, 2% conductive agent, and 3% binder SBR;
[0088] Example 2-2: (2) Preparation of negative electrode sheet: the active material contains 90% artificial graphite, 5% hard carbon, 2% conductive agent, and 3% binder SBR;
[0089] Example 2-3: (2) Preparation of negative electrode sheet: the active material contains 91% artificial graphite, 4% hard carbon, 2% conductive agent, and 3% binder SBR;
[0090] Example 2-4: (2) Preparation of negative electrode sheet: The active material contains 53% artificial graphite, 42% hard carbon, 2% conductive agent, and 3% binder SBR.
[0091] Example 3 Group
[0092] The third embodiment group was carried out with reference to the first embodiment, except that the width of the insulating glue coated on the positive electrode sheet insulating layer was changed, and the width of the side edge of the insulating layer (inactive area) of the positive electrode sheet along the first direction was changed to exceed the same side edge of the negative electrode sheet along the first direction (referred to as the insulating layer exceeding the negative electrode sheet in Table 1), see Table 1 and Table 2 for details:
[0093] Example 3-1: (4) Battery assembly: One side edge of the insulating layer (inactive area) of the positive electrode sheet along the first direction exceeds the same side edge of the negative electrode sheet along the first direction by 0.5 mm, and the width of the insulating layer is 2.5 mm;
[0094] Example 3-2: (4) Battery assembly: One side edge of the insulating layer (inactive area) of the positive electrode sheet along the first direction exceeds the same side edge of the negative electrode sheet along the first direction by 3 mm, and the width of the insulating layer is 5 mm;
[0095] Example 3-3: (4) Battery assembly: One side edge of the insulating layer (inactive area) of the positive electrode sheet along the first direction exceeds the same side edge of the negative electrode sheet along the first direction by 5 mm, and the width of the insulating layer is 7 mm.
[0096] Example 3-4: (4) Battery assembly: One side edge of the insulating layer (inactive area) of the positive electrode sheet along the first direction exceeds the same side edge of the negative electrode sheet along the first direction by 0.1 mm, and the width of the insulating layer is 2.1 mm.
[0097] Example 4 Group
[0098] The fourth embodiment is carried out in accordance with the first embodiment, the only difference being that the size of the electrode die-cutting sheet is changed, thereby changing the percentage value A of the overhang area to the total area of the negative electrode sheet, as shown in Table 1 and Table 2:
[0099] Example 4-1: (3) Pole sheet die-cutting: Punch the positive electrode sheet to 64.6 mm (60.6 mm paste + 4 mm insulation glue) mm*45 mm; punch the negative electrode sheet to 66 mm*47 mm; the percentage value A of the overhang area to the total area of the negative electrode sheet is 12%, wherein the width of the overhang area of the edge of the negative electrode sheet close to the insulating layer of the positive electrode sheet is 2 mm, and the width of the overhang area of the edge of the other side is 3.4 mm, the width ratio of the negative electrode sheet to the positive electrode active area in the first direction of the positive electrode sheet is 1.09:1, and the area ratio of the negative electrode sheet to the positive electrode active area is 1.14:1;
[0100] Example 4-2: (3) Pole sheet die-cutting: Punch the positive electrode sheet to 68.8 mm (64.8 mm paste + 4 mm insulation glue) mm*45 mm; punch the negative electrode sheet to 66 mm*47 mm; the percentage value A of the overhang area to the total area of the negative electrode sheet is 6%, wherein the width of the overhang area of the edge of the negative electrode sheet close to the insulating layer of the positive electrode sheet is 1 mm, and the width of the overhang area of the edge of the other side is 0.2 mm, the width ratio of the negative electrode sheet to the positive electrode active area in the first direction of the positive electrode sheet is 1.02:1, and the area ratio of the negative electrode sheet to the positive electrode active area is 1.06:1;
[0101] Example 4-3: (3) Pole sheet die-cutting: punch the positive electrode sheet to 62.5mm (58.5mm paste + 4mm insulating glue) mm*45mm; punch the negative electrode sheet to 66mm*47mm; the percentage value A of the overhang area to the total area of the negative electrode sheet is 15%, wherein the width of the overhang area of the edge of the negative electrode sheet close to the insulating layer of the positive electrode sheet is 2mm, and the width of the overhang area of the other edge is 5.5mm, the width ratio of the negative electrode sheet to the positive electrode active area in the first direction of the positive electrode sheet is 1.12:1, and the area ratio of the negative electrode sheet to the positive electrode active area is 1.19:1.
[0102] Example 5 Group
[0103] Example 5 was carried out in accordance with Example 1, except that the particle size Dv50 of the hard carbon was changed, as shown in Table 1 and Table 2:
[0104] Example 5-1: (2) Preparation of negative electrode sheet: The particle size Dv50 of hard carbon is 3.5 μm. According to step (1), it can be calculated that the ratio of the particle size Dv50 of the positive electrode active material to the particle size Dv50 of the hard carbon is 1.1:1;
[0105] Example 5-2: (2) Preparation of negative electrode sheet: The particle size Dv50 of hard carbon is 1.5 μm. According to step (1), it can be calculated that the ratio of the particle size Dv50 of the positive electrode active material to the particle size Dv50 of the hard carbon is 2.7:1;
[0106] Example 5-3: (2) Preparation of negative electrode sheet: The particle size Dv50 of hard carbon is 4.8 μm. According to step (1), it can be calculated that the ratio of the particle size Dv50 of the positive electrode active material to the particle size Dv50 of the hard carbon is 0.8:1.
[0107] Example 6 Group
[0108] Example 6 was carried out in accordance with Example 1, except that the amount of 1,3-propane sultone (PS) additive added to the electrolyte was changed, as shown in Table 1:
[0109] Example 6-1: (4) Battery assembly: 0.6% PS was used as an electrolyte additive;
[0110] Example 6-2: (4) Battery assembly: 1.5% PS was used as an electrolyte additive;
[0111] Example 6-3: (4) Battery assembly: Using 0% PS as electrolyte additive (no PS additive is used).
[0112] Example 7 Group
[0113] Example 7 was carried out in accordance with Example 1, with the only difference being that the particle size Dv50 of the positive electrode active material was changed, as shown in Table 1 and Table 2:
[0114] Example 7-1: (1) Preparation of positive electrode sheet: The particle size Dv50 of the positive electrode active material is 3.5 μm, and the ratio of the particle size Dv50 of the positive electrode active material to the particle size Dv50 of the hard carbon is 1.4:1;
[0115] Example 7-2: (1) Preparation of positive electrode sheet: The particle size Dv50 of the positive electrode active material is 4.5 μm, and the ratio of the particle size Dv50 of the positive electrode active material to the particle size Dv50 of the hard carbon is 1.8:1;
[0116] Example 7-3: (1) Preparation of positive electrode sheet: The particle size Dv50 of the positive electrode active material is 3 μm, and the ratio of the particle size Dv50 of the positive electrode active material to the particle size Dv50 of the hard carbon is 1.2:1;
[0117] Example 7-4: (1) Preparation of positive electrode sheet: The particle size Dv50 of the positive electrode active material is 5 μm, and the ratio of the particle size Dv50 of the positive electrode active material to the particle size Dv50 of the hard carbon is 2:1.
[0118] Example 8 Group
[0119] Example 8 was carried out in accordance with Example 1, except that the mass percentage content D of the element Co in the positive electrode active material was changed, as shown in Table 1 and Table 2:
[0120] Example 8-1: LiNi 0.6 Co 0.085 Mn 0.315 O2, D is 11%;
[0121] Example 8-2: LiNi 0.6 Co 0.115 Mn 0.285 O2, D is 13%.
[0122] Example 9 Group
[0123] Example 9 was carried out in accordance with Example 1, except that the amount of 1,3-propane sultone (PS) additive added to the electrolyte was changed, and the mass percentage content D of the element Co in the positive electrode active material was changed, as shown in Table 1 and Table 2:
[0124] Example 9-1: LiNi 0.6 Co 0.125 Mn 0.275 O2, D is 15%, (4) Battery assembly: 0.5% PS is used as electrolyte additive;
[0125] Example 9-2: LiNi 0.6 Co 0.075 Mn 0.325 O2, D is 10%, (4) Battery assembly: 2% PS is used as electrolyte additive.
[0126] Example 10
[0127] Example 10 is carried out with reference to Example 1, with the only difference being that, during the battery assembly process, an E-type stack is used to form a bare cell, as shown in Tables 1 and 2 for details.
[0128] Comparative Example 1
[0129] Comparative Example 1 was carried out with reference to Example 1, except that the mass percentage content B of the hard carbon in the negative electrode active material was changed, as shown in Table 1 and Table 2:
[0130] (2) Preparation of negative electrode sheet: The active material contains 95% artificial graphite, 2% conductive agent, and 3% binder SBR (without hard carbon).
[0131] Comparative Example 2
[0132] Comparative Example 2 is carried out with reference to Example 1, except that the size of the electrode die-cutting sheet is changed, thereby changing the percentage value A of the overhang area to the total area of the negative electrode sheet, and changing the mass percentage content B of the hard carbon in the negative electrode active material. For details, see Table 1 and Table 2:
[0133] (3) Pole sheet die-cutting: Punch the positive electrode sheet to 62.5 mm (58.5 mm paste + 4 mm insulation glue) mm*45 mm; punch the negative electrode sheet to 66 mm*47 mm; the percentage value A of the overhang area to the total area of the negative electrode sheet is 15%, wherein the width of the overhang area at one edge is 2 mm, and the width of the overhang area at the other edge is 5.5 mm, the width ratio of the negative electrode sheet to the positive electrode active area in the first direction of the positive electrode sheet is 1.12:1, and the area ratio of the negative electrode sheet to the positive electrode active area is 1.19:1;
[0134] (2) Preparation of negative electrode sheet: The active material contains 65% artificial graphite, 30% hard carbon, 2% conductive agent, and 3% binder SBR.
[0135] Comparative Example 3
[0136] Comparative Example 3 is carried out with reference to Example 1, except that the size of the electrode die-cutting sheet is changed, thereby changing the percentage value A of the overhang area to the total area of the negative electrode sheet, and changing the mass percentage content B of the hard carbon in the negative electrode active material. For details, see Table 1 and Table 2:
[0137] (3) Pole sheet die-cutting: Punch the positive electrode sheet to 68.8 mm (64.8 mm paste + 4 mm insulation glue) mm*45 mm; punch the negative electrode sheet to 66 mm*47 mm; the percentage value A of the overhang area to the total area of the negative electrode sheet is 6%, wherein the width of the overhang area of the edge of the negative electrode sheet close to the insulation layer of the positive electrode sheet is 1 mm, and the width of the overhang area of the edge of the other side is 0.2 mm, the width ratio of the negative electrode sheet to the positive electrode active area in the first direction of the positive electrode sheet is 1.02:1, and the area ratio of the negative electrode sheet to the positive electrode active area is 1.06:1;
[0138] (2) Preparation of negative electrode sheet: The active material contains 91% artificial graphite, 4% hard carbon, 2% conductive agent, and 3% binder SBR.
[0139] Comparative Example 4
[0140] Comparative Example 4 is carried out with reference to Example 1, except that the width of the insulating glue coated on the positive electrode sheet insulating layer is changed, and the width of the side edge of the insulating layer (inactive area) of the positive electrode sheet along the first direction is changed to exceed the same side edge of the negative electrode sheet along the first direction (referred to as the insulating layer exceeding the negative electrode sheet in Table 1), see Table 1 and Table 2 for details:
[0141] (4) Battery assembly: One side edge of the insulating layer (inactive area) of the positive electrode sheet along the first direction exceeds the same side edge of the negative electrode sheet along the first direction by 0 mm (does not exceed the negative electrode), and the width of the insulating layer is 2 mm.
[0142] Table 1
[0143]
[0144] Table 2
[0145]
[0146]
[0147] Lithium-ion battery test example
[0148] (1) Power performance test:
[0149] The lithium-ion batteries prepared in the above examples and comparative examples were discharged at 25°C, 50% SOC, constant current 10C for 3s;
[0150] a. At 25°C, the lithium-ion batteries prepared in the above embodiments and comparative examples were capacitated: 1C discharge to the lower limit voltage, 1C charge to the upper limit voltage, and then 1C discharge to the lower limit voltage. The capacity discharged was recorded as C0 (initial capacity);
[0151] b. Charge at 1C to the upper limit voltage, and discharge at 1C for 30 minutes to adjust the battery cell to 50% SOC;
[0152] c. Use 10C0 constant current discharge for 3s, and finally record the terminal voltage (V) after the lithium-ion battery power test discharge, as shown in Table 3.
[0153] (2) Capacity retention rate of lithium-ion battery at 60°C calendar life:
[0154] a. At 25°C, the lithium-ion batteries prepared in the above embodiments and comparative examples were capacitated: 1C discharge to the lower limit voltage, 1C charge to the upper limit voltage, and then 1C discharge to the lower limit voltage. The capacity released is recorded as C0 (initial capacity); 1C charge to the upper limit voltage (full charge storage);
[0155] b. Store at 60℃ for 45 days;
[0156] c. After storage, the battery cell is discharged to the lower limit voltage at 1C at 25°C, charged to the upper limit voltage at 1C, and then discharged to the lower limit voltage at 1C. The discharged capacity is recorded as C1 (capacity after storage); C1 / C0 is recorded as the storage capacity retention rate (%) of the lithium-ion battery at 60°C calendar life, as shown in Table 3 for details.
[0157] The specific method is to measure the capacity retention rate of the battery cell after 60 days of storage.
[0158] (3) Acupuncture pass rate test:
[0159] 1C / 1C makes C0, 1C fully charged, 1C discharge to 80% SOC (discharge 20% C0 capacity end); the battery uses a high temperature resistant steel needle with a diameter of ф3.00mm (the cone angle of the needle tip is 45°-60°, the surface of the needle is smooth and free of rust, oxide layer and oil), penetrates from the direction perpendicular to the battery plate at a speed of (80mm±5mm / s), and the puncture position should be close to the geometric center of the punctured surface (the steel needle stays in the battery). Observe for 1h. Determine whether the battery cell will catch fire. If it catches fire, the battery cell will not pass the puncture. If it does not catch fire, it is determined that the battery cell can pass the puncture; repeat the above test several times, and calculate the puncture pass (%) of the puncture test, as shown in Table 3.
[0160] Table 3
[0161]
[0162]
[0163] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A lithium ion battery, characterized in that: The lithium-ion battery comprises a negative electrode sheet and a positive electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating located on at least one side of the surface of the negative electrode current collector; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active coating located on at least one side of the surface of the positive electrode current collector; the lithium-ion battery is a laminated battery; in the thickness direction of the negative electrode sheet, the negative electrode active coating at least covers the positive electrode active coating; The lithium-ion battery comprises a negative electrode ear and a positive electrode ear, and along a first direction, the negative electrode sheet is connected to the negative electrode ear, and the positive electrode sheet is connected to the positive electrode ear; The negative electrode sheet includes an overhang area, which refers to the portion of the negative electrode sheet corresponding to the non-overlapping area of the projections of the negative electrode active coating and the positive electrode active coating along the thickness direction of the negative electrode sheet, and the percentage of the area of the overhang area to the total area of the negative electrode sheet is recorded as A; The negative electrode active coating comprises a negative electrode active material, the negative electrode active material comprises hard carbon, and the mass percentage content of the hard carbon in the negative electrode active material is recorded as B; A and B satisfy the relationship: 0.003≤A×B≤0.
036.
2. The lithium-ion battery according to claim 1, characterized in that The A is 6%-12%, preferably 8%-10%; And / or, the B is 5%-30%, preferably 10%-30%.
3. The lithium-ion battery according to claim 1, characterized in that The width of the overhang area of the edge of any side of the negative electrode sheet in the first direction is 0.1 mm-5 mm, preferably 1 mm-3 mm.
4. The lithium-ion battery according to claim 1, characterized in that: The positive electrode current collector includes a positive electrode active region and a positive electrode inactive region, the positive electrode inactive region is located at the edge in the first direction, the positive electrode active region is connected to the positive electrode inactive region, the positive electrode active coating is arranged in the positive electrode active region, and the positive electrode inactive region is arranged with an insulating layer; Along the first direction, an edge of the negative electrode sheet close to the positive electrode inactive region does not exceed an edge of the positive electrode inactive region away from the positive electrode active region.
5. The lithium-ion battery according to claim 4, characterized in that: Along the first direction, an edge of the positive electrode inactive region away from the positive electrode active region exceeds an edge of the negative electrode sheet close to the positive electrode inactive region by 0.5 mm to 3 mm.
6. The lithium-ion battery according to claim 4, characterized in that: The width ratio of the negative electrode sheet to the positive electrode active area in the first direction is (1.03-1.08):1; And / or, the area ratio of the negative electrode sheet to the positive electrode active area is (1-1.1):
1.
7. The lithium-ion battery according to claim 1, characterized in that: The positive electrode active coating comprises a positive electrode active material, and the positive electrode active material comprises Li (1+x) Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; wherein M is at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo and Zr, and the positive electrode active material includes secondary particles formed by primary particles; Preferably, the ratio of the particle size Dv50 of the positive electrode active material to the particle size Dv50 of the hard carbon is (1-2.1):
1.
8. The lithium-ion battery according to claim 7, characterized in that: The particle size Dv50 of the positive electrode active material is 3.5 μm-4.5 μm; And / or, the particle size Dv50 of the hard carbon is 2 μm-3.5 μm.
9. The lithium-ion battery according to claim 7, characterized in that: The lithium-ion battery further includes an electrolyte, the electrolyte includes 1,3-propane sultone, and the mass percentage content of the 1,3-propane sultone is C based on the total mass of the electrolyte; the mass percentage content of the element Co is D based on the total mass of the positive electrode active material; The C and the D satisfy the relationship: 0.05≤C / D≤0.
12.
10. The lithium ion battery according to claim 9, characterized in that: The C is 0.6%-1.5%; and / or, the D is 11%-13%.
Citation Information
Patent Citations
Lithium ion battery electrode structure, preparation method and lithium ion battery comprising lithium ion battery electrode structure
CN114388733A
Method for improving electrochemical pre-lithiation rate
CN115020834A
Negative pole piece and lithium ion battery
CN115224237A
Secondary battery and electric device
CN116525766A
Positive plate, electrochemical device and preparation method thereof
CN117038850A
Cited By
Battery monomer, battery device and electric equipment
CN121885731A